Banks and monetary transmission in Europe: empirical evidence - DE BONDT G.J., G.J. (PSL Quarterly Review, 2013)
The present work examines bank lending behaviour in continental Europe. An empirical analysis is performed using bank-level panel data for fiscal years 1990-1995 to investigate the existence of a bank lending and balance sheet channel in Europe. The results reveal that monetary policy in continental Europe matter most for small banks and for banks with relatively illiquid balance sheets. Most of the findings point to the existence of a bank lending channel in Germany and the Netherlands. JEL Codes: G21